Sustainable urbanization in Southeast Asia and beyond: Challenges of population growth, land use change, and environmental health - Arfanuzzaman, Md; Dahiya, Bharat (Growth and change, 2019)
As economic growth centres, the Southeast Asian cities feature high population pressure, unsustainable land use, environmental degradation, and large ecological footprints. It is difficult to manage environmental health and basic services for urban dwellers, and ensure optimum flow of ecosystem services in the context of rapid, unplanned, and haphazard urbanization. These challenges are particularly multifaceted in the developing countries of Southeast Asian region. This study, based on secondary sources, adopted multidisciplinary lenses, such as geographical information systems, socio‐economic perspective, and sustainability science to examine the population situation, land use change pattern, and drivers of environmental degradation in the Southeast Asian cities as well as the Dhaka megacity, and brought forth a fresh perspective to look into contemporary urban ecosystems, population dynamics, environmental health, and sustainability. It also focused on identifying the commonalities among the cities under study to create a common understanding towards promoting collaborative urban development. This study shows that the urbanization process in the Southeast Asia region is taking place mostly in an unplanned and haphazard manner. With little concern for nature, life‐supporting ecological systems, and the environment, urban spatial growth continues unabated. The data surveyed and discussed in this paper shows that the current style of urbanization in Southeast Asia can best be called unsustainable. The findings also suggest that the general wellbeing and welfare of the current and future generations in Southeast Asian cities as well as in Dhaka is at risk. The paper recommends concerted efforts towards making the urbanization process sustainable, including better urban planning, policymaking, and international and regional cooperation.